Palimpsests of the romantic - Karner, Christian; Kazmierczak, Marek (Taylor & Francis, 2016)
This articles offers a longue durée perspective to illustrate that just as romanticism was a necessary, though not single-handedly sufficient condition for nationalist movements of the 19th century, an understanding of later cultural and political phenomena – including contemporary neo-nationalisms – benefits from an appreciation of the romantics’ continuing, albeit often unacknowledged legacy. Empirically, we make this argument through select and carefully contextualized Polish and Austrian discursive ‘snapshots’. Conceptually, we propose that new theoretical terminology is needed, which we find in what we describe and analyse as palimpsests of the romantic. Key assumptions and sentiments that defined romanticism are thereby shown to be re- and over-written, under novel social conditions and by later generations of political and cultural actors in both Poland and Austria.